Dominance, diversity, and niche breadth in arbuscular mycorrhizal fungal communities - John Davison; Martti Vasar; Siim‐Kaarel Sepp; Jane Oja; Saleh Al‐Quraishy; C. Guillermo Bueno; Juan José Cantero; Ezequiel Chimbioputo Fabiano; Guillaume Decocq; Lauchlan Fraser; Inga Hiiesalu; Wael N. Hozzein; et al. (Ecology, 2022)
Classical theory identifies resource competition as the major structuring force of biotic communities and predicts that (i) levels of dominance and richness in communities are inversely related, (ii) narrow niches allow dense “packing” in niche space and thus promote diversity, and (iii) dominants are generalists with wide niches, such that locally abundant taxa also exhibit wide distributions. Current empirical support, however, is mixed. We tested these expectations using published data on arbuscular mycorrhizal (AM) fungal community composition worldwide. We recorded the expected negative relationship between dominance and richness and, to a degree, the positive association between local and global dominance. However, contrary to expectations, dominance was pronounced in communities where more specialists were present and, conversely, richness was higher in communities with more generalists. Thus, resource competition and niche packing appear to be of limited importance in AM fungal community assembly; rather, patterns of dominance and diversity seem more consistent with habitat filtering and stochastic processes.